THE INFLUENCE OF PRODUCTS, AND PROMOTIONS ON THE INTEREST IN SAVING - Novita, Anti Anggriani; Sukarniati, Lestari (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2022)
The presence of sharia banks in Bima apart from hoping that people will use sharia banks as a place for borrowing capital, the government also hopes that the people of Bima city can save or save their money in sharia banks. to determine the influence of profit sharing, products and promotions on the interest in saving of the people of Bima City at Bank NTB Syariah. descriptive research method with multiple linear regression analysis techniques, quantitative research type, using primary data, population of 161,362 people and sample of 100. The research results This shows that the profit sharing variable has a positive effect on interest in saving if the distribution of benefits has a coefficient value of 0.035. This shows that the product variable has a good influence on Curious about Saving if the item has an assessment coefficient of 0.058. This shows that the promotion variable has a positive influence on the feeling of wanting to save if the increase has a coefficient value of 0.747. The table shows that the important value of the item variable (X2) is 0.349 > 0.05. This shows that item (X2) and interest in saving (Y) do not have a crucial influence on each other. The table shows that 0.000 is a crucial value for the Progress variable (X3). This shows that Interest in Saving (Y) and Promotion (X3) have a big influence on each other. can be seen based on the emergence of data using the F test which states that the components of profit sharing, products and promotions simultaneously or mutually influence each other greatly influence interest in saving at Bank NTB Syariah Bima Kota.or can be seen in the data which shows Fcount > F table (440,494 > 1.96). Conclusion Given that the number of tests increases each year, future analyzes should perform more tests to ensure that the data collected is more accurate.